Que bom viver a vida: memórias e histórias de mulheres que sobreviveram à violência da ditadura. - Souza, Jonatas Xavier de (2013)
This work is appealing for the universe of memories and feelings of women, political prisoners during the military dictatorship in Brazil (1964 - 1985), who survived the traumatic experience of lucid torture. Having as a main source movie Que Bom Te Ver Viva, full length documentar produced by Lúcia Murat from 1988 - 1989. We assume that the art of Lucia Murat in Que Bom Te Ver Viva meets, while self consciousness and memory that is human history, the function of raising individual particularities, writing it self, the generically human. In this perspective, grasp the film as an important means of production, dissemination and reception of individual and collective experiences of the past and presente, and thereby as a material linked to identity and social dimensions that are justified from their membership of a historical culture formed in the time of the events, the circumstances of film production. Indeed, analyzing the images of orality and Que Bom Te Ver Viva, means, Immediately talk to a social representation that contributes to a historical and cultural participation of women in the armed struggle against the dictatorship, the discourser of the Brazilian feminist movement in the 1980s, such as: violence against women, women's sexual freedom, gender relations and power involving sexes.